The Role of the Election Supervisory Agency in Enforcement of Violations of the 2020 Simultaneous Regional Head Election in Berau Regency - Jamhari, Jamhari; Handoko, V Rudy; Maduwinarti, Ayun (Indonesian Journal of Advanced Research, 2024)
This research discusses the role of the Election Supervisory Agency in the prosecution of the handling of violations of the 2020 Berau Regency Simultaneous Pilkada. This research is a descriptive qualitative research with data collection techniques from the interview process, observation and documentation. The research focuses on identifying and analysing Bawaslu's role in prosecuting administrative violations and criminal violations of the elections, identifying and analysing obstacles to prosecuting the handling of election violations, and developing a model for prosecuting the handling of election violations. The results showed that Bawaslu's role in enforcing the handling of violations of the 2020 Berau Regency Pilkada has been carried out quite well both in handling administrative violations and handling criminal violations. The obstacles faced by Bawaslu in the efforts to enforce the handling of violations of the 2020 Berau Regency Pilkada are the lack of human resources (HR) in Bawaslu Berau Regency, the lack of public awareness to participate in monitoring Pilkada violations, and the massive practice of money politics. The existing conditions for the handling of election violations through Gakkumundu formed by Bawaslu with inter-institutional collaboration with the Police and the Prosecutor's Office. For the reform model, the researcher proposes a draft model for strengthening Bawaslu's authority in integrated law enforcement by adopting the authority of OTT and TT carried out by the KPK and Cyber Pungli and the design of an Ad Hoc election judicial model for the effectiveness of election dispute resolution.